Effect of Long-Lived Species Generated by Non-Thermal Plasmas on the Auto-Ignition Delay of Liquid Hydrocarbon Fuel-Air Pre-Mixtures. Issue 9 (2nd September 2017) - Ono, Takuma; Segawa, Takehiko; Saito, Naoaki; Takahashi, Eiichi; Nishioka, Makihito
ABSTRACT: The effect of long-lived species induced by irradiation of air/fuel mixtures with non-thermal plasmas was studied to understand the mechanism of plasma-assisted ignition. The dependence of auto-ignition delay on temperature was measured using a rapid compression and expansion machine. Mixtures of air with i -octane, primary reference fuel, or methylcyclohexane as fuels were passed through the non-thermal plasma at the intake generated by surface dielectric barrier discharge before compression. The ignition delay was observed to be shortened owing to the effect of long-lived intermediate species such as NOx in the pre-mixture. This shortening behavior was found to be similar to those in compression experiments with NOx externally added. However, the presence of NOx only partly explained the results. Other species in the plasma-irradiated gas were identified by a chemical detecting tube and mass spectrometry with ion attachment ionization. The role of other species in inducing ignition-delay shortening was discussed with chemical kinetic simulations.